Carbon-rich shungite as a natural resource for efficient Li-ion battery electrodes. (April 2018) - Chou, Nam Hawn; Pierce, Neal; Lei, Yu; Perea-López, Nestor; Fujisawa, Kazunori; Subramanian, Shruti; Robinson, Joshua A.; Chen, Gugang; Omichi, Kaoru; Rozhkov, Sergey S.; Rozhkova, Natalia N.; Terrones, Mauricio; et al.
Abstract: A wide variety of synthetic carbon allotropes embrace tremendous potential for energy storage applications. There have been number of reports on the synthesis of carbonaceous anode materials with lithium (Li) storage capacity larger than the theoretical limit for graphite (372 mAh/g, corresponding to LiC6 ). However, besides the performance, available resources and cost efficiency are obstacles that could hinder their exploitation. Here we present carbon-rich Precambrian rock "shungite" as a natural resource for a Li-ion battery anode. It is found that upon structural modification the energy density of fully lithiated "shungite" can exceed the density of graphite, becoming comparable to non-graphitizable ("hard") carbon. High-resolution transmission electron microscopy (HRTEM) studies of modified "shungite" suggest that it consist of spatially arranged fractals of bended, curved, mono- or stacked graphene layers. By analyzing the features of 7 Li Nuclear Magnetic Resonance (NMR) spectra of fully lithiated "shungite" we conclude that the enhanced storage capacity is mainly due to the presence of open edge few layered graphene flakes. We thus suggest carbon-rich "shungite" as an alternative and effective natural resource for Li-ion battery electrodes. Graphical abstract: Image 1